Compositional Analysis, Antioxidant and Antimicrobial Potential of the Seed of Annona cinerea Dunal Grown in Nigeria (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: Annona cinerea; phytochemical; free radical scavenging; antimicrobial activities